2012
DOI: 10.1159/000341454
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Expression of TGF-�1 and CTGF in Human Mesangial Cells byExendin-4, a Glucagon-like Peptide-1Receptor Agonist

Abstract: Background: Despite the presence of glucagon-like peptide-1 receptor (GLP-1R) in kidney tissues, its direct effect on diabetic nephropathy remains unclear. The transforming growth factor-β1 (TGF-β1) and the connective tissue growth factor (CTGF) both induce extracellular matrix accumulation and persistent fibrosis in the glomerular mesangium of patients with diabetic nephropathy. Objective: Herein, we demonstrate that a GLP-1R agonist, exendin-4, exerts renoprotective effects through its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
2
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 39 publications
1
38
2
3
Order By: Relevance
“…46 Limei et al reported that DPP-4 inhibitor sitagliptin administered to hypertensive rats spontaneously improved endothelial function by restoring nitric oxide bioavailability. 47 Glorie et al reported that DPP-4 inhibitor vildagliptin attenuated AKI in a rat ischemia-reperfusion model.…”
Section: Discussionmentioning
confidence: 99%
“…46 Limei et al reported that DPP-4 inhibitor sitagliptin administered to hypertensive rats spontaneously improved endothelial function by restoring nitric oxide bioavailability. 47 Glorie et al reported that DPP-4 inhibitor vildagliptin attenuated AKI in a rat ischemia-reperfusion model.…”
Section: Discussionmentioning
confidence: 99%
“…В экспериментах на лабораторных крысах с СД-1 применение эксендина-4 способствовало уменьшению альбуминурии, гипертрофии клубочков, макрофагальной инфильтрации клубочков, снижению развития фиброза и тубулопатии вне зависимости от уровня глюкозы в крови [34]. В исследованиях in vitro с использованием культур мезангиальных клеток человека применение агонистов рецептора ГПП-1 способствовало снижению экспрессии одного из основных профиброгенных факторов -транс-формирующего фактора роста β-1 [35].…”
Section: Discussionunclassified
“…Эксендин-4 ослаблял нарушение функ-ции почек в моделях никотинового повреждения почек и при изнурительных физических нагрузках [32]. В усло-виях in vitro эксендин-4 подавлял пролиферацию мезан-гиоцитов, индуцированную избытком глюкозы [33,34]. При этом снижалась секреция фибронектина и экс-прессия TGFβ1 и фактора роста соединительной ткани (CTGF) [33].…”
Section: влияние аналогов гпп-1 и ингибиторов дпп-4 на развитие патолunclassified
“…В усло-виях in vitro эксендин-4 подавлял пролиферацию мезан-гиоцитов, индуцированную избытком глюкозы [33,34]. При этом снижалась секреция фибронектина и экс-прессия TGFβ1 и фактора роста соединительной ткани (CTGF) [33]. Таким образом, нефропротективный эф-фект эксендина-4 и его синтетического аналога эксе-натида может быть реализован вне сахароснижающего действия этих веществ.…”
Section: влияние аналогов гпп-1 и ингибиторов дпп-4 на развитие патолunclassified